(untitled) (LACCEI, 2024)
The semi-arid climate conditions in the Chanduy community, province of Santa Elena (Ecuador), coupled with a significant deficit in drinking water coverage, are leading to severe water shortages. New approaches are needed to reduce the high natural water salinity, thus increasing the overall water availability in this area. This research aims to evaluate an advanced water treatment technology named “Electrodialysis” for desalination purposes to meet the population’s basic needs and promote economic development ofn the community. Surface water and groundwater samples were collected to characterize the in-situ physicochemical parameters and major ions. The electrodialysis technology has decreased the concentration of total dissolved solids (TDS) down to the threshold values of 500-600 mg/L, recommended by the World Health Organization (WHO) for consumption purposes.. The system presented a low energy consumption (0.72 kWh/m3), resulting in a low treatment cost of USD 0.07 per m3. The optimal operational condition of the electrodialysis system was 6 V arranged in a stack of 6 cell pairs to desalinate 500 mL of synthetic water in 30 minutes. This work contributes to achieving the Sustainable Development Goals N° 6 “Clean Water and Sanitation” and N° 11 “Sustainable Cities and Communities” in semi-arid water scarity area.